Subchondral Bone Regenerative Effect of Two Different Biomaterials in the Same Patient - Marco Cavallo; Roberto Buda; Francesca Vannini; Francesco Castagnini; Alberto Ruffilli; Sandro Giannini (Case Reports in Orthopedics)
This case report aims at highlighting the different effects on subchondral bone regeneration of two different biomaterials in the same patient, in addition to bone marrow derived cell transplantation (BMDCT) in ankle. A 15-year-old boy underwent a first BMDCT on a hyaluronate membrane to treat a deep osteochondral lesion (8 mm). The procedure failed: subchondral bone was still present at MRI. Two years after the first operation, the same procedure was performed on a collagen membrane with DBM filling the defect. After one year, AOFAS score was 100 points, and MRI showed a complete filling of the defect. The T2 mapping MRI after one year showed chondral tissue with values in the range of hyaline cartilage. In this case, DBM and the collagen membrane were demonstrated to be good biomaterials to restore subchondral bone: this is a critical step towards the regeneration of a healthy hyaline cartilage.